The corrosion behavior of EW75 magnesium alloy in the research vessel KEXUE during the ocean voyage - Quantong Jiang; Dongzhu Lu; Liren Cheng; Nazhen Liu; Lihui Yang; Baorong Hou (npj Materials Degradation, 2022)
Abstract The corrosion behavior of EW75 magnesium alloy in the Research Vessel KEXUE (RV KEXUE) during the ocean voyage was researched. The weight loss, corrosion depths, corrosion morphologies, and corrosion products were all analyzed. The mean weight loss rate of EW75 alloy Extrusion Surface was 0.0672 mg cm−2 y−1 (0.0903 mm y−1) after exposure corrosion tests, whereas that of Cross-section Surface was 0.0938 mg cm−2 y−1 (0.1537 mm y−1). Both extrusion direction and transverse direction of magnesium alloy samples occurred the brittle fracture in the harsh marine environment, and the mechanical strength fell precipitously after the exposure tests. The corrosion resistance of EW75 magnesium alloys obviously showed the anisotropy, which was due to the texture of the magnesium alloy in the microstructure. High salinity and high humidity environment led to a severe corrosion of EW75 magnesium alloys during exposure in the RV KEXUE during the ocean voyage. This study will provide the effective data for the service of magnesium alloys in typical marine atmospheric environment.